CASE STUDY: THE DESIRABLE CHARACTERISTICS OF GRADUATES FOR THE IMPROVEMENT OF THE BACHELOR OF EDUCATION PROGRAM (FOUR-YEAR PROGRAM) IN PHYSICS, CHEMISTRY, BIOLOGY AND MATHEMATICS, FACULTY OF SCIENCE, NAKHON PHANOM UNIVERSITY - Gunnula, Wuttichai; Wattananualsakul, Thanaporn; Srivarom, Wissarut; Namkhang, Pornpan; Anuchaivong, Patchalai (Journal of MCU Nakhondhat, 2024)
This research aims to develop and refine the curriculum for teaching and learning, alongside assessing the quality requirements for graduates across various qualification levels. The objective is to ensure that these standards are congruent with the aspirations of prospective students and the expectations of employers. The quality of graduates is paramount for higher education institutions, as it facilitates the production of graduates who exhibit the desired attributes delineated in the Higher Education Qualifications Framework. To this end, the researcher conducted a comprehensive survey on the attributes deemed desirable for graduates, ensuring their alignment with both contemporary and future societal demands. This article addresses the following key points: 1) To explore the demand for the Faculty of Science at Nakhon Phanom University to offer a Bachelor of Education program, 2) To assess the desired attributes of teachers within the Bachelor of Education (four-year program) in the fields of Science and Mathematics at the Faculty of Science, Nakhon Phanom University, and 3) To inquire about the level of professional competencies that graduates of the Bachelor of Education (four-year program) should possess, in alignment with the established scope of professional teaching competencies. This investigation employed a quantitative research methodology, utilizing a questionnaire to collect data from 512 participants. The statistical analyses included frequency distribution, percentage, mean, and standard deviation. The findings indicate that the most highly regarded attribute for graduates is a "teacher’s spirit," which is consistent with the mission of producing and nurturing graduates who embody this quality and possess a strong moral conscience, in alignment with the philosophical underpinnings of the Faculty of Science at Nakhon Phanom University.